TRANSDERMAL DRUG DELIVERY SYSTEM: ADVANTAGES AND LIMITATIONS (International Journal of Food and Nutritional Sciences, 2022)
Human civilizations have used chemicals as aesthetic and therapeutic agents on the skin for thousands of years. The use of the skin as a medicine delivery method did not begin until the 20th century, however. In reality, Merriam Webster dates the term "transdermal" to 1944, underscoring the fact that it is a relatively new idea in the field of medicine and pharmaceuticals. Transdermal medications come in distinct, self-contained dose forms. Drug distribution via the skin to have an overall impact without causing changes in the drug's plasma concentration. This review article briefly discusses the benefits of transdermal drug delivery systems (TDDS), skin channels for TDDS, basic clinical concerns in using TDDS, and TDDS limitations. Because of the patches' significant benefits over alternative controlled drug delivery methods, their effectiveness has been shown.